KUANTITAS DAN POTENSI MATA AIR KABUPATEN JAYAWIJAYA DAN TOLIKARA PROVINSI PAPUA - Eric A. Patandianan (INTAN Jurnal Penelitian Tambang, 2019)
Papua Province, especially the Central Mountain Region, which experience regional expansion will certainly experience increased in the need of clean water. The spring found in Jayawijaya and Tolikara Regencies actually has a high potential for water resources if optimized for utilization. Therefore, research is needed on the potential of springs in both regencies so that this study can be continued towards the development of efficient management of spring water resources. Priority scales based on potential springs in the development of planning the provision of raw water sources with uncritical classification in Jayawijaya District can be carried out in Walelagama District, where the fulfillment of domestic water needs can be met by Goa Spring, Asokobal District where fulfillment of domestic water needs can be met by the Hepuba 1 Spring, Hepuba 2 Spring and Hepuba 3 Spring, Maima District where fulfillment of domestic water needs can be fulfilled by Waima 1 and Waima 2 Springs. Whereas in Tolikara Regency can be done in Wenam District where fulfillment of domestic water needs can be met by Yelepelek and Lirak Springs, District Anawi where fulfillment of domestic water needs can be fulfilled by Anawi 1 and Anawi 2 Springs, Kubu District where fulfillment of domestic water needs can be fulfilled by Minagi Spring.